Density Functional Theory Calculation of Zn and N Codoped Graphene for Oxygen Reduction and Evolution Reactions. Issue 9 (13th August 2020) - Li, Yongcheng; Hu, Riming; Wan, Xin; Shang, Jia‐Xiang; Wang, Fu‐He; Shui, Jianglan
Abstract: The highly efficient and low‐cost electrocatalysts are of great importance for energy conversion systems such as fuel cells, metal–air batteries, and water electrolyzers. Here, the activities of oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in zinc and nitrogen codoped graphene with different zinc–nitrogen (Zn–N) coordination numbers and configurations are studied by density functional theory (DFT) calculations. The calculation results show that both Zn–N coordination numbers and structure configurations affect the activities of ORR and OER on ZnN x sites. Among all the calculated structures, ZnN4 ‐pyridine shows the lowest ORR overpotential of 0.61 V, whereas ZnN4 ‐pyrrole and ZnN4 ‐edge show lower OER overpotentials of 0.73 and 0.63 V, respectively. However, the other low N coordination structures of ZnN x ‐pyridine/pyrrole/edge ( x = 1/0/1–3) demonstrate poor activities. The electronic structure reveals that the O‐p orbital shows moderate hybridization strength with the N‐p and Zn‐d orbitals in O adsorbed ZnN4 systems thus facilitates the electrocatalytic reactions. The findings shed light on the rational design of bifunctional electrocatalysts for energy storage and conversion. Abstract : The structure of ZnN4 ‐pyridine shows lower oxygen reduction reaction (ORR) overpotentials of 0.61 V, whereas ZnN4 ‐pyrrole and ZnN4 ‐edge show lower oxygen evolution reaction (OER) overpotentials of 0.73 and 0.63 V,  respectively. However, the other low N coordination structures of ZnN x ‐pyridine/pyrrole/edge ( x = 1/0/1–3) demonstrate poor activities.